Towards Inclusive Growth: Community-Centered Management Strategies for SMEs - Elpisah, E. (Golden Ratio of Community Services and Dedication, 2023)
This research explores the impact of community-centered management strategies on Small and Medium Enterprises (SMEs) and their surrounding communities, aiming to uncover insights into fostering inclusive growth. Employing a systematic literature review, the study synthesizes existing research to analyze the implications of such strategies on SME performance, resilience, and socio-economic development. The methodological approach involves the examination of key empirical studies and theoretical frameworks to elucidate the multifaceted dimensions of community-centered management. Findings indicate a positive correlation between SME engagement in community practices, such as Corporate Social Responsibility (CSR) activities and stakeholder engagement, and enhanced financial performance, competitiveness, and societal well-being. Moreover, the research highlights the critical role of organizational culture, leadership commitment, and institutional support in driving SME involvement in community development initiatives. Despite the potential benefits, challenges such as resource constraints, lack of awareness, and regulatory hurdles hinder SMEs' adoption of community-centered practices. However, collaborative efforts among stakeholders from various sectors can mitigate these barriers and create an enabling environment for SMEs to embrace sustainable business practices. Overall, this study underscores the importance of community-centered management strategies in advancing inclusive growth and sustainable development agendas. The findings contribute to scholarly understanding and inform evidence-based policymaking and practice aimed at promoting SME resilience and socio-economic progress.